Grain Sorghum and Palmer Amaranth (Amaranthus palmeri) Response to Herbicide Programs and Agronomic Practices. (15th September 2017) - Besançon, Thierry E.; Heiniger, Ronnie W.; Weisz, Randy; Everman, Wesley J.
Abstract : Weed control remains a major challenge for economically viable grain sorghum production in the southeastern United States due to crop sensitivity to weed competition during early growth stages. Field experiments were conducted in 2012 and 2013 to determine the effects of grain sorghum row spacing, population density, and herbicide programs on Palmer amaranth control, crop growth, and grain yield. Treatments included row spacings of 19, 38, and 76 cm; grain sorghum population densities of 99, 000, 198, 000, 297, 000, and 396, 000 plants ha −1 ; and three herbicide programs: (1) a nontreated control, (2) S -metolachlor at 1, 410 g ai ha −1 plus atrazine at 1, 820 g ha −1 PRE, and (3) S -metolachlor at 1, 070 g ha −1 plus atrazine at 1, 380 g ha −1 PRE followed by 2, 4 D at 330 g ha −1 POST. Palmer amaranth control benefited from the addition of a POST herbicide and from crop density ≥297, 000 plants ha −1 . Under weedy conditions, Palmer amaranth density was not affected by narrower row spacing or increased crop density, whereas its dry biomass was reduced by 33% with 19 and 38 compared to 76 cm rows, and by 43% with ≥297, 000 vs 99, 000 plants ha −1 . Row spacing had no effect on light interception by the crop canopy. However, crop density influenced canopy closure with maximum light interception occurring one and a half weeks earlier for density ≥297, 000 plants ha −1 . Yield increased by 18% for 19 vs 38 and 76 cm rows, whereas grain crop density had no effect. Overall, these results indicate that the combination of row spacing≤30 cm and crop density ≥297, 000 plants ha −1 provided at least 97% Palmer amaranth control in the absence of POST application and reduced its biomass by 32% in nontreated plots compared to 76 cm row spacing and crop density≤198, 000 plants ha −1 .